Concentration of circulating immune complexes in experimental generalized inflammatory process in animals of different age under action of immunomodulators - Kovalenko, T; Klimova, Ye; Minukhin, V (Annals of Mechnikov's Institute, 2020)
Under physiological conditions a formation and a presence of the CEC in liquids is one of the manifestations of the immune response to receipt of antigens and an important factor, which provides immunity. Circulating immune complexes act as agents involved in the regulation of immune response and maintaining communication between the immune system and other regulatory systems of the body and direction to his defense. The intensity of the formation of the CEC may vary under the influence of infectious antigens and immune preparations. Material and methods. Material for the experiment were white male rats 3 months of age ("young") weighing 100 -140gr. (n = 40) and 22-month ("old") weighing 200 -240 g. (n = 40). And the first (n=10) and second (n=10) groups of rats served as controls. Third (n=15) and fourth (n=15) group of animals was injected intraperitoneal daily agar culture of Pseudomonas aeruginosa № 27835 ATCC (injected with 1.5 ml suspension of bacteria, which contained 109 CFU/ml). Fifth (n=15) and sixth (n=15) groups of animals were injected intraperitoneally daily agar culture of Escherichia coli number 25592, ATCC (injected with 1.5 ml of bacteria suspension which contain 109 CFU/ml). Control animals were taken from the experiment by decapitation 3rd day – n=20. Control and infected animals were taken from the experiment by decapitation at 3rd day - n=27, 5th day – n=27 and 7th day – n=26. In the second phase of the experiment Ia (n = 6) and IIa (n = 6) were the control group of rats following administration of the experimental composite preparation consisting amino acids, nucleotides, enzymes, vitamins (MF). In two age groups of animals with inflammation induced by E. coli suspension treated with MF 20 mсl 3-month rats (IIIa group n = 6) and 40 mсl 22-month rats (IVa group n = 6). Ib (n = 6) and IIb (n = 6) were the control group of rats after the injection of comparison, containing mannitol and natural antioxidant betakaroten (PO). In two age groups of animals with inflammation induced by E. coli suspension treated with PO 0,5 ml 3-month rats (IIIb group n = 6) and 1 ml 22-month rats (IVb group n = 6). Control animals were taken from the experiment by decapitation on 3rd day - n = 12. Infected animals were taken from the experiment by decapitation on 3rd day - n = 12 and 7th day - n = 12. Results and discussion. One of the biological functions of the immunoglobulins is neutralization antigens to form circulating immune complexes. In the work it was shown that the induction of inflammation of P.aeruginosa and E.coli suspension in experimental animals of two age groups led to the increase of the CEC in serum compared to control animals. After administration experimental composite preparation comprising amino acids, nucleotides, enzymes and vitamins (MF) in young animals with inflammation induced by E. coli suspension was revealed an increase the CEC, compared with an older group of animals throughout the experiment. When adding formulation containing mannitol and natural antioxidant betacarotene (РО), in the animals two age groups intensity CEC formation depended on the sequence of adding of suspension E. coli and immunomodulator PО. Was revealed elevated levels of CEC only, in those animals which immunocorrector PО was given to induce an inflammatory response. Conclusion. In the control group of animals older age (22 months) the CEC concentration was 2 times lower than in the young (3 months) control animals. After the action of bacterial suspensions P.aeruginosa and E.coli formation CEC intensity was significantly increased in both age groups of experimental animals, indicating the activation of antigen binding immunoglobulin infection. The action of the immunocorrective composite peptide drug MF significantly inhibited the formation of the CEC only in older animals throughout the experiment. With the addition of immunocorrector PО revealed increase of the CEC in young and old animals to induce inflammatory of bacterial suspension E.coli.